Ensembl 2019. Issue Volume 47:Issue D1(2019) (8th November 2018) - Cunningham, Fiona; Achuthan, Premanand; Akanni, Wasiu; Allen, James; Amode, M Ridwan; Armean, Irina M; Bennett, Ruth; Bhai, Jyothish; Billis, Konstantinos; Boddu, Sanjay; Cummins, Carla; Davidson, Claire; et al.
Abstract: The Ensembl project (https://www.ensembl.org ) makes key genomic data sets available to the entire scientific community without restrictions. Ensembl seeks to be a fundamental resource driving scientific progress by creating, maintaining and updating reference genome annotation and comparative genomics resources. This year we describe our new and expanded gene, variant and comparative annotation capabilities, which led to a 50% increase in the number of vertebrate genomes we support. We have also doubled the number of available human variants and added regulatory regions for many mouse cell types and developmental stages. Our data sets and tools are available via the Ensembl website as well as a through a RESTful webservice, Perl application programming interface and as data files for download.